Effectiveness of caregiver-oriented transitional care program in promoting preparedness of caregivers for home care of burn patients. - Dualan, Jun Jun A. (2018)
Unpreparedness of caregivers of burn patients can result to several complications at post-discharge period (Zwicker, 2010; Agency for Healthcare Research and Quality, 2012). The Alfredo T. Ramirez Burn Center (ATRBC) in the Philippine General Hospital (PGH) has documented several burn morbidity and mortality that occurred post hospital discharge. Psychological conditions, contracture, infection and even death are just a few of many complications. In contrary to the previous practice, current trend in burns involve sending the patient home with a burn dressing and follows-up as outpatient for wound inspection and evaluation. This is favorable to healthcare facility as it can cater for those who sustained majors burns and of serious cases in times when it is prudent to discharge the stable ones; furthermore, early discharge can reduce healthcare costs in the part of patient and family. However, this change in burn management requires also a change in the nursing system. At present, there is limited evidence in preparing caregivers of burns patients for home care, and that the ATRBC PGH has no structured discharge teaching program for the caregivers of burn patients that are required to enrich the caregivers with skills for home care of burns. Considering the recommended style and structure of teaching program, the investigator developed the Caregiver-oriented Transitional Care Program (CTCP) and studied its effectiveness in promoting preparedness of caregivers for home care of burn patients. -- This study aimed to compare the preparedness of caregivers before and after conducting the CTCP; to explore relationship between the preparedness and patient and caregiver factors after undergoing the CTCP; and to compare handwashing competency, wound dressing competency and medication administration hassle before and after conducting the CTCP. -- One-group pre-and-posttest quasi-experimental design was used to study thirty (30) adult caregivers of burn patient that were recruited by convenience sampling in the ATRBC PGH between November 2017 to March 2018. CTCP was conducted in a three-part session using lecture and demonstration with the aid of videos and written instructional materials. Caregivers were evaluated in terms of preparedness using Preparedness for Caregivers Scale (PCS) pre and post CTCP (primary outcome). Secondary outcomes were included such as handwashing competency through the Handwashing Accuracy Score (HAS), wound dressing competency utilizing Wound Dressing Accuracy Score (WDAS) and medication administration hassle using Family Medication Administration Hassles Scale (FCMAHS). All the measurements were content valid and reliable. -- At alpha of 0.05, data analysis revealed statistically significant results favoring the use of CTCP. Preparedness (p 0.000), handwashing competency (0.000), wound dressing competency (p 0.000) and medication administration hassle (0.000) improved after receiving the structured teaching intervention. Furthermore, potential confounders such as caregivers and patient factors failed to establish a significant relationship with preparedness.